Impartial Umpireships : The General Motors UAW Experience - Alexander, Gabriel (Relations industrielles / Industrial Relations, 1959)
This article is a chapter of the just published book, Arbitration and the Law, proceedings of the 1959 meeting of the National Academy of Arbitrators. –Author's note